Nilai Sufistik dalam Penguatan Relasi Guru–Murid pada Pendidikan Islam - Mas Faiqul Khuluq; Didi Junaedi (Ideguru: Jurnal Karya Ilmiah Guru, 2026)
The transformation of modern education has influenced the pattern of teacher–student relations in Islamic education. The dominance of academic, administrative, and cognitive achievement orientations has caused educational relationships to become increasingly formal and technical, while moral and spiritual dimensions have weakened. This condition contributes to the decline of adab, exemplary conduct, and ethical closeness between teachers and students in the educational process. This article aims to analyze the role of Sufi values in strengthening teacher–student relations within contemporary Islamic education. The study employed a qualitative approach using a library research design through conceptual analysis of literature related to Islamic education, Sufism, and educational relations. Data were collected through documentation studies of relevant scholarly sources and analyzed using content analysis and critical interpretation techniques. The findings indicate that Sufi values such as adab, sincerity, exemplary behavior, moral responsibility, and spiritual guidance play an important role in developing humanistic and transformative educational relationships. These values can serve as an alternative foundation for strengthening teacher–student relations amid the challenges of modern education, which tend to be pragmatic and materially oriented. This study implies the importance of integrating moral and spiritual dimensions into Islamic educational practices in order to establish more holistic and character-oriented educational relationships.